Johannebergsrallyt - Development of a realistic 3D rally game using open-source tools - Edström, Sofia; Fägerlind, Erik; Lundholm, Erik; Sandell, Victor; Severin, Joel (My University, 2015)
Independent developers seek success by developing near AAA-grade game using limited time and development resources. In this thesis, we explore some of the different aspects these developers face. In a small team, with a short time frame, we developed a networked rally game in 3D, focusing on real-time computer graphics. We investigate how in-house developed features and already available open-source software could be used in achieving this goal, aiming for real-time performance on the mid-end consumer hardware of today (2015). It became clear that, given the limited development resources, only a handful of the features and graphical effects an AAA-grade game features could be supported. The effects that were successfully implemented include car enamel reflections, skid marks, particle systems, bloom, motion blur, shadows and screen-space ambient occlusion (SSAO). Additionally, a basic platform for rally car physics and networked multi-player support was developed.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science